If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + 3i)(4 + -1i) = 0 Multiply (2 + 3i) * (4 + -1i) (2(4 + -1i) + 3i * (4 + -1i)) = 0 ((4 * 2 + -1i * 2) + 3i * (4 + -1i)) = 0 ((8 + -2i) + 3i * (4 + -1i)) = 0 (8 + -2i + (4 * 3i + -1i * 3i)) = 0 (8 + -2i + (12i + -3i2)) = 0 Combine like terms: -2i + 12i = 10i (8 + 10i + -3i2) = 0 Solving 8 + 10i + -3i2 = 0 Solving for variable 'i'. Factor a trinomial. (4 + -1i)(2 + 3i) = 0Subproblem 1
Set the factor '(4 + -1i)' equal to zero and attempt to solve: Simplifying 4 + -1i = 0 Solving 4 + -1i = 0 Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1i = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1i = 0 + -4 -1i = 0 + -4 Combine like terms: 0 + -4 = -4 -1i = -4 Divide each side by '-1'. i = 4 Simplifying i = 4Subproblem 2
Set the factor '(2 + 3i)' equal to zero and attempt to solve: Simplifying 2 + 3i = 0 Solving 2 + 3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3i = 0 + -2 3i = 0 + -2 Combine like terms: 0 + -2 = -2 3i = -2 Divide each side by '3'. i = -0.6666666667 Simplifying i = -0.6666666667Solution
i = {4, -0.6666666667}
| -6(7v-5)-3=3(v-6) | | -17=19-12m | | 4x+6=5x-12 | | X+4.5=8.7 | | 0.2x+3=28 | | 1.3+x=-1.6 | | V+6=-12 | | S=52+2.75p | | -1+3(x+2)=5(1+8x) | | -(2y-12+(-y))=-33 | | Y^4+y^3-4y-16=0 | | 5x+12=108-10x | | 1.3+-1.6= | | (4x)-(3x)+(2x)=24 | | 9+2j=5 | | 8m=7(7x-1) | | 18.84=2(3.14) | | 0.3(32)+x=0.3(20+x) | | 11x+45=2x | | (5-6i)(3-2i)=0 | | 3q+10=7 | | 7-(6x+2)=(x-12)+3 | | 2a+9=5a-6 | | x=18-2/3 | | 6+x=54 | | 67-39= | | 9.4=x-17 | | 2a+9=5a+6 | | .05x+.10(19-x)=1.55 | | 27=.9(200-a) | | 2x+3m-5x+7m= | | -3y-9=6y+18 |